Preparation method of blow-off prevention porous carbon material for silicon-carbon negative electrode

Through emulsifier compounding and drying agglomeration technology, anti-blowing porous carbon materials are prepared, which solves the problem of material blowing during the activation process of spherical porous carbon materials, improves yield and reduces costs, while maintaining the material Formographic stability and particle size uniformity, it is suitable for silicon-carbon negative electrode materials.

CN119263273AActive Publication Date: 2025-01-07BEIJING IAMETAL NEW ENERGY TECH CO LTD +1

Patent Information

Application Number
CN202411526901.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-07
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The existing spherical porous carbon materials have the problem of material being blown during gas activation, which leads to low activation yield and high manufacturing cost, which affects the internal stability of the battery.

Method used

Spherical resin aggregates are prepared by emulsifier compounding method, and the preparation and dry agglomeration of solvents, emulsifiers, nucleating agents and curing agents are combined with pyrolytic carbonization and gas activation to form a porous carbon material that is anti-blow loss.

Benefits of technology

It improves activation yield, reduces manufacturing costs, maintains the morphological stability of spherical materials, enhances the fluidity and particle size distribution uniformity of porous carbon materials, and reduces the volume expansion effect of silicon materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263273A_ABST
    Figure CN119263273A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of an anti-blow-off porous carbon material for a silicon-carbon negative electrode, which comprises the following steps: (S1) preparing a solvent, an emulsifier and a nucleating agent into a mixed solution, adding a resin oligomer and a curing agent, polymerizing into spherical resin under the condition of stirring at 40-80 DEG C, and drying and agglomerating into blocks; the emulsifier comprises a micromolecule anionic surfactant and a polymer emulsifier; (S2) crushing and screening to obtain spherical agglomerates with proper particle sizes, and pyrolyzing and carbonizing the spherical agglomerates in an inert atmosphere to obtain pyrolytic carbon; (S3) performing activated pore-forming on the pyrolytic carbon in an activated atmosphere to obtain an activated carbon aggregate; and (S4) depolymerizing and separating the activated carbon aggregate to obtain the porous carbon material. According to the invention, the spherical particles are greatly agglomerated, the pain point of gas blow-off in the industrial activation process is solved, the activation yield is improved, and meanwhile, the mechanical properties of the material can be adjusted by controlling the crosslinking degree.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of negative electrode materials for lithium-ion batteries, and is mainly used for the preparation of silicon-carbon negative electrode materials, and specifically relates to a method for preparing a blow-off-proof porous carbon material for silicon-carbon negative electrodes. Background Art

[0002] At present, secondary batteries have become the focus of the new energy field because of their advantages of reuse. Especially in the field of power batteries, higher requirements are placed on battery capacity. Silicon-based negative electrode materials are currently lithium-ion battery negative electrode materials with application prospects, but silicon-based negative electrode materials are prone to volume expansion during use, which eventually leads to battery capacity decay. Carbon materials have a smaller volume expansion effect. In silicon-carbon composite materials, the carbon matrix can form a better buffer layer to slow down volume expansion. However, under high pressure, irregularly shaped carbon-based materials will split the current collector, causing an internal short circuit in the battery. In order to solve the drawbacks of irregularly shaped carbon, researchers have proposed the idea of ​​spherical porous carbon.

[0003] However, there are spherical porous carbon precursors on the market, and there is a disadvantage of material being blown away during the gas activation process. At present, rotary kilns are used for activation in the field of porous carbon activation. Activation gas is continuously introduced during the activation process, and the metal filter element is an important component of the activation furnace. At present, the minimum pore size limit of metal filter elements in the industry is 10μm, which causes a large amount of carbon powder to be carried away by the activation gas during the activation process, causing the raw material to be blown away. After the material is blown away, the gas-solid ratio of the activation gas to the raw material changes, which ultimately affects the stability of the activation process and causes a sharp increase in the cost of porous carbon materials.

[0004] The resin ball preparation method provided by the present invention adopts the emulsifier compounding method to emulsify into balls. In the drying process, the weak connection effect of the emulsifier is utilized to agglomerate the resin balls into polymers within a certain particle size range, thereby preventing the sample from being blown away during the activation process, increasing the activation yield, and providing a good idea for industrial production. Summary of the invention

[0005] The purpose of the present invention is to solve the problem that the existing spherical resin has serious blow-off during gas activation, resulting in low activated carbon yield and high manufacturing cost. In order to achieve the purpose of the present invention, a spherical resin aggregate is prepared using a resin oligomer as a raw material and an emulsification system containing a polymer binder. The present invention solves the above technical problems through the following technical solutions.

[0006] A method for preparing a blow-off-proof porous carbon material for a silicon-carbon negative electrode comprises the following steps:

[0007] (S1) preparing a mixed solution of a solvent, an emulsifier and a nucleating agent, adding a resin oligomer and a curing agent, polymerizing into a spherical resin under stirring conditions at 40-80° C., and drying and agglomerating into a mass; the emulsifier comprises a small molecule anionic surfactant and a polymer emulsifier;

[0008] (S2) crushing and screening to obtain spherical agglomerates of suitable particle size, and pyrolyzing and carbonizing the spherical agglomerates under an inert atmosphere to obtain pyrolytic carbon;

[0009] (S3) activating and pore-forming the pyrolytic carbon in an activation atmosphere to obtain activated carbon aggregates;

[0010] (S4) Activating the carbon aggregates for depolymerization and separation to obtain a porous carbon material.

[0011] Furthermore, in step (S1), the resin oligomer is selected from at least one of a phenolic resin oligomer and an acrylonitrile oligomer, and the weight average molecular weight of the resin oligomer is 1000-3000.

[0012] Furthermore, in step (S1), the mass ratio of the solvent, the emulsifier, the nucleating agent, the polymer precursor and the curing agent is 100:1-5:1-5:30-50:1-10.

[0013] Further, in step (S1), the solvent is a mixed solvent of water and C1-3 alcohol, and the C1-3 alcohol is selected from methanol, ethanol, and propanol; the alcohol accounts for 1-5wt% in the solvent; further, the solvent is a mixed solvent of water, C1-3 alcohol, and an organic solvent miscible with water; the organic solvent is selected from dimethylformamide, cyclopentane sulfone, and dimethyl sulfoxide, and the organic solvent accounts for 1-5wt%. The addition of alcohol and / or organic solvent can change the surface tension of the system, increase the water solubility of the oligomer, and facilitate the rapid dispersion of the oligomer precursor and the solvent at the initial stage of the polymerization reaction. If alcohol and organic solvent are not added, it will be difficult for the polymerization system to quickly form an emulsion. When the weight average molecular weight of the resin oligomer is below 1500, a mixed solvent of water and C1-3 alcohol is used; when the weight average molecular weight of the resin oligomer is greater than 1500, an organic solvent is also added.

[0014] Furthermore, in step (S1), the anionic surfactant is selected from at least one of sodium dodecyl sulfate and sodium dodecylbenzene sulfonate; the polymer emulsifier is selected from at least one of gum arabic powder, polyvinyl alcohol, polyethylene glycol, F127, PVP, and P123, and the molecular weight of the polymer emulsifier is 1000-5000, preferably 2000-3000.

[0015] Furthermore, the mass ratio of the anionic surfactant to the polymer emulsifier is 6-10:1.

[0016] Further, in step (S1), the nucleating agent is selected from at least one of sodium chloride, anhydrous sodium sulfate, ammonium carbonate, ammonium acetate, and ammonium bicarbonate; the curing agent is selected from at least one of urotropine, N,N'-methylenebisacrylamide, p-toluenesulfonic acid, phenolsulfonic acid, and oxalic acid. Further, in step (S1), drying is not particularly limited and is well known in the art, such as drying or vacuum drying.

[0017] Furthermore, in step (S2), the suitable particle size is controlled by screening to be 30-100 mesh, and the particles that fail the screening can be put into the emulsion waste liquid and dried into blocks again to achieve the purpose of recycling. The inert atmosphere includes but is not limited to at least one of nitrogen, helium, and argon.

[0018] Furthermore, in step (S2), the process conditions of pyrolysis carbonization are 600-800°C and pyrolysis time is 1-10h.

[0019] Furthermore, in step (S3), the activation atmosphere includes but is not limited to at least one of carbon dioxide and water vapor, the activation temperature is 800-1200° C., and the activation time is 5-20 hours.

[0020] Furthermore, in step (S4), the deagglomeration separation uses a powder deagglomeration and dispersion machine, the purpose of which is to deagglomerate the agglomerated activated carbon aggregates to obtain porous carbon with a suitable particle size.

[0021] The porous carbon product obtained by the preparation method provided by the present invention has a sphericity rate of ≥90%, a surface morphology without rough particles, and a uniform particle size distribution. It has good fluidity during powder compaction and can fill the voids. At the same time, the particle size of the resin microspheres in the technical solution is controllable and can be matched with the silicon material to reduce the volume expansion effect of the silicon material.

[0022] Compared with the prior art, the preparation method provided by the present invention is to form resin into balls by emulsification, dry and aggregate into blocks, carbonize, crush, and activate with gas. Among them, a high molecular weight emulsifier is selected to be compounded with a low molecular weight surfactant, which acts as a dispersant and an adhesive at the same time, so that the spherical particles form larger agglomerates, and the agglomerates are connected by force, and the depolymerization treatment after activation does not cause morphological damage. In the industrial activation process, the problem of gas loss is solved and a good spherical morphology is maintained. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is the SEM image of the activated carbon obtained in step (S3) of Example 1.

[0024] Figure 2 This is the SEM image of the porous carbon material obtained in Example 1.

[0025] Figure 3This is the SEM image of the porous carbon product obtained in Comparative Example 2.

[0026] Figure 4 This is the particle size distribution diagram of the porous carbon product obtained in Example 1. DETAILED DESCRIPTION

[0027] In order to more clearly explain the technical solution of the present invention, the technical solution of the present invention will be fully described below. Obviously, the described embodiments are only some cases of the present invention, and the present invention is not limited to the following embodiments.

[0028] Example 1

[0029] (S1) 6.80 g of polyethylene glycol (PEG 2000, number average molecular weight 2000), 0.76 g of sodium dodecyl sulfate (emulsifier dosage is 3.78 wt% of water), and 2.00 g of ethanol are added to 200.00 g of water, and stirred at 500 r / min at 30° C., and then 10 g of NaCl is added as a nucleating agent to prepare a solution, and then 60 g of low molecular weight phenolic resin (weight average molecular weight is about 1500) and 2.5 g of oxalic acid are added as a curing agent (the curing agent dosage is 1.25 wt% of water), dispersed at 30° C. for 4 h, reacted at 95° C. for 24 h, and an emulsion is obtained after the reaction is completed. The emulsion is subjected to solid-liquid separation, and the separated solid is dried in a blast oven for 24 h at a drying temperature of 80° C. to obtain block-shaped spherical resin aggregates; the weight average molecular weight of the oligomer precursor in Example 1 is about 1500, and it can be well dispersed in the solution, so there is no need to add an additional organic solvent;

[0030] (S2) The dried and agglomerated block resin is screened into 100 mesh particles by a jaw crusher roller; the unqualified small-size resin is dispersed into the emulsion waste liquid and dried into blocks again to achieve the purpose of recycling; the screened spherical resin particles are pyrolyzed and carbonized in an argon atmosphere at a pyrolysis temperature of 700° C. and a pyrolysis time of 2 hours to obtain pyrolytic carbon;

[0031] (S3) activating the pyrolytic carbon, wherein the activation gas is CO2, the activation temperature is 900°C, and the activation time is 12 hours to obtain activated carbon aggregates;

[0032] (S4) The activated carbon aggregates are deagglomerated in a powder deagglomeration and disintegration machine to obtain monodisperse spherical particles, that is, the product is a porous carbon material for preventing blow-off of silicon-carbon negative electrodes.

[0033] Figure 1 This is a SEM image of the activated carbon obtained in step (S3) of Example 1; Figure 2 This is a SEM image of the anti-blowout porous carbon material of the silicon-carbon negative electrode product obtained in Example 1. Figure 4 This is the particle size distribution diagram of the porous carbon product obtained in Example 1.

[0034] Example 2

[0035] The other conditions are the same as those in Example 1, except that in step (S1), the amount of polyethylene glycol used is 3.4 g, and the amount of sodium dodecyl sulfate used is 0.38 g, that is, the amount of emulsifier used is 1.89% of water.

[0036] Example 3

[0037] The other conditions are the same as those in Example 1, except that in step (S1), the amount of polyethylene glycol used is 1.7 g, and the amount of sodium dodecyl sulfate used is 0.19 g, that is, the amount of emulsifier used is 0.945% of water.

[0038] Example 4

[0039] The other conditions are the same as those in Example 1, except that in step (S1), the amount of oxalic acid added is 5 g, and the amount of curing agent used is 2.5 wt % of water.

[0040] Example 5

[0041] The other conditions are the same as those in Example 1, except that in step (S1), the amount of oxalic acid added is 10 g, and the amount of curing agent used is 5 wt % of water.

[0042] Example 6

[0043] The other conditions are the same as those in Example 1, except that in step (S1), the amount of oxalic acid added is 20 g, and the amount of curing agent used is 10 wt % of water.

[0044] Example 7

[0045] (S1) 9.2 g of polyethylene glycol (PEG 2000, number average molecular weight 2000), 1.0 g of sodium dodecyl sulfate (emulsifier dosage is 3.78 wt% of water), 5.0 g of ethanol, and 8.0 g of cyclopentane sulfone are added to 200.00 g of water, and stirred at 500 r / min at 30° C., then 10 g of Na2SO4 nucleating tester is added to prepare a solution, and then 60 g of acrylonitrile oligomer (weight average molecular weight is about 3000) and 5 g of N, N'-methylenebisacrylamide as a curing agent (curing agent dosage is 2 wt% of water) are added, dispersed at 30° C. for 4 h, reacted at 95° C. for 24 h, and an emulsion is obtained after the reaction is completed. The emulsion is subjected to solid-liquid separation, and the separated solid is dried in a blast oven for 24 h at a drying temperature of 80° C. to obtain block-shaped spherical resin aggregates; in Example 1, the weight average molecular weight of the oligomer precursor is about 3000, and an organic solvent cyclopentane sulfone needs to be additionally added;

[0046] The subsequent steps (S2) to (S4) are the same as those in Example 1.

[0047] Comparative Example 1

[0048] The other conditions are the same as those in Example 1, except that in step (S1), the emulsifier is 7.56 g polyethylene glycol, that is, sodium lauryl sulfate is not added. In comparative example 1, step (S5) cannot be depolymerized smoothly, indicating that the emulsifier lacks anionic surfactant and cannot be depolymerized smoothly.

[0049] Comparative Example 2

[0050] Other conditions were the same as those in Example 1, except that in step (S1), the emulsifier was 7.56 g of sodium dodecyl sulfate, i.e., no polyethylene glycol was added.

[0051] Figure 3 The SEM image of the porous carbon obtained in Comparative Example 2. The porous carbon obtained in Comparative Example 2 has a low sphericity, polyethylene glycol is missing in the emulsifier, and the resin cannot be spherical; this indicates that the polymerization reaction requires the selection of an emulsifier that is compatible with the reaction system in order to successfully obtain a spherical resin. If it cannot be spherical, the irregular carbon-based material will have the risk of splitting the current collector under high pressure conditions, thereby causing a short circuit inside the battery. From a design perspective, the edges and corners of the irregular carbon are reduced and prepared into a spherical morphology. The present invention uses a compound of a small molecule anionic surfactant and a certain amount of polyethylene glycol as an emulsifier to smoothly make the resin spherical.

[0052] The Dv50 of the emulsion obtained in step (S1) of Example 1 is 10.16 μm, and the particle size of the block-shaped spherical resin aggregates after solid-liquid separation and drying is 50.26 μm. The Dv50 of the corresponding emulsion of Comparative Example 2 is 9.52 μm, and the particle size of the block-shaped spherical resin aggregates after solid-liquid separation and drying is 15.63 μm. It can be seen that in the emulsion state, the average particle size difference is not large. After drying, in Example 1, the spheres are obviously agglomerated, resulting in an increase in particle size.

[0053] Example 1

[0054] The particle size of the pyrolytic carbon obtained in the above embodiment and comparative example step (S2) was tested, and the results are shown in Table 1 below.

[0055] Table 1 Product particle size analysis

[0056]

[0057] As can be seen from Table 1, the particle size can be regulated by regulating the emulsifier content. The hydroxyl groups in the polymer emulsifier extend to the water end by reacting with water; the hydrophobic groups and the resin molecules are adsorbed together due to the electrostatic force, which protects the resin droplets. The polymer emulsifier can significantly reduce the interfacial tension between the resin and the water phase, thereby reducing the surface free energy between the two phases and maintaining the thermodynamic stability of the polymerization system. Then the resin is dispersed into oil droplets of corresponding sizes under stirring. When the concentration of the polymer emulsifier is low, the emulsifier molecules attached to the surface of a single droplet will decrease, the protective ability of the droplet will be weakened, and the polymerization between the resins will easily occur, and the particle size of the resin balls finally formed will be large. When the concentration of the polymer emulsifier is high, the protective ability of the droplets will be enhanced, and the particle size of the resin balls formed will be smaller. After adding the polymer emulsifier, the proportion of fine powder is low, indicating that agglomeration has been formed; without adding the polymer emulsifier, the proportion of fine powder is high, indicating that good agglomeration has not been formed. In Comparative Example 2, the proportion of fine powder > 800 mesh in the pyrolysis carbon recovery material is very high, indicating that good agglomeration is not formed.

[0058] The porous carbon materials obtained in the above examples and comparative examples were tested for pore structure, yield and maximum bearing pressure, and the results are shown in Table 2. The yield is obtained by dividing the discharge amount of the industrial activation furnace after reaction by the amount of pyrolysis carbon powder added before activation. The lower the yield, the more serious the blow-off, resulting in increased production costs.

[0059] Table 2 Performance test of porous carbon materials

[0060]

[0061] It can be seen from Table 2 that the porous carbon prepared by the present invention has a micropore ratio of more than 90% and a certain mesopore ratio, a yield of more than 40%, and has good mechanical properties.

[0062] Application Examples

[0063] The porous carbon material and silane gas obtained in the above embodiments and comparative examples were subjected to silicon deposition under nitrogen as carrier gas conditions. The silicon deposition process conditions were: 500-600°C, deposition time: 4-9h, so that the silicon content in the obtained composite silicon-carbon material was about 50wt%, and the electrochemical performance was tested. The battery composition was: the positive electrode was a lithium sheet; the negative electrode was a silicon-carbon composite material coated on a copper foil and then cut, and the rest was a double-layer PP / PE separator and an electrolyte 1mol / L LiPF6 (the solvent was a mixture of diethyl carbonate, dimethyl carbonate and ethylene carbonate in a volume ratio of 1:1:1). The test conditions were: a blue electric test system, and the charge and discharge test was performed between 0.005-1.5V. The results are shown in Table 3 below.

[0064] Table 3 Electrochemical performance test

[0065]

[0066] As can be seen from Table 3, the silicon-carbon composite negative electrode material prepared by the present invention and supported by silicon deposition has excellent electrochemical properties. Although the electrochemical performance of the finished product prepared by pressing the porous carbon is reduced, the reduction is very small and within an acceptable range. However, the preparation method of the present invention significantly improves the loss caused by blowing during the preparation of porous carbon, saves costs, and has more industrial advantages.

Claims

1. A method for preparing a blow-off-proof porous carbon material for a silicon-carbon negative electrode, characterized in that: The following steps are involved: (S1) preparing a mixed solution of a solvent, an emulsifier and a nucleating agent, adding a resin oligomer and a curing agent, polymerizing into a spherical resin under stirring conditions at 40-80° C., and drying and agglomerating into a mass; the emulsifier comprises a small molecule anionic surfactant and a polymer emulsifier; (S2) crushing and screening to obtain spherical agglomerates of suitable particle size, and pyrolyzing and carbonizing the spherical agglomerates under an inert atmosphere to obtain pyrolytic carbon; (S3) activating and pore-forming the pyrolytic carbon in an activation atmosphere to obtain activated carbon aggregates; (S4) Activating the carbon aggregates for depolymerization and separation to obtain a porous carbon material.

2. The preparation method according to claim 1, characterized in that: In step (S1), the resin oligomer is selected from at least one of a phenolic resin oligomer and an acrylonitrile oligomer; and the weight average molecular weight of the resin oligomer is 1000-3000.

3. The preparation method according to claim 1, characterized in that: In step (S1), the mass ratio of the solvent, the emulsifier, the nucleating agent, the polymer precursor and the curing agent is 100:1-5:1-5:30-50:1-10.

4. The preparation method according to claim 1, characterized in that: In step (S1), the solvent is a mixed solvent of water and C1-3 alcohol, the C1-3 alcohol is selected from methanol, ethanol, and propanol; the alcohol accounts for 1-5wt% in the solvent; further, the solvent is a mixed solvent of water, C1-3 alcohol, and an organic solvent miscible with water; the organic solvent is selected from dimethylformamide, cyclopentane sulfone, and dimethyl sulfoxide, and the organic solvent accounts for 1-5wt%.

5. The preparation method according to claim 4, characterized in that: When the weight average molecular weight of the resin oligomer is below 1500, a mixed solvent of water and C1-3 alcohol is used; when the weight average molecular weight of the resin oligomer is greater than 1500, an organic solvent is also added.

6. The preparation method according to claim 1, characterized in that: In step (S1), the anionic surfactant is selected from at least one of sodium dodecyl sulfate and sodium dodecylbenzene sulfonate; the polymer emulsifier is selected from at least one of gum arabic powder, polyvinyl alcohol, polyethylene glycol, F127, PVP, and P123, and the molecular weight of the polymer emulsifier is 1000-5000, preferably 2000-3000.

7. The preparation method according to claim 6, characterized in that: The mass ratio of the anionic surfactant to the polymer emulsifier is 6-10:

1.

8. The preparation method according to claim 1, characterized in that: In step (S1), the nucleating agent is selected from at least one of sodium chloride, anhydrous sodium sulfate, ammonium carbonate, ammonium acetate, and ammonium bicarbonate; and the curing agent is selected from at least one of urotropine, N,N'-methylenebisacrylamide, p-toluenesulfonic acid, phenolsulfonic acid, and oxalic acid.

9. The preparation method according to claim 1, characterized in that: In step (S2), the suitable particle size is controlled by screening to be 30-100 mesh; the inert atmosphere includes but is not limited to at least one of nitrogen, helium, and argon; Furthermore, in step (S2), the process conditions of pyrolysis carbonization are 600-800°C and pyrolysis time is 1-10h.

10. The preparation method according to claim 1, characterized in that: In step (S3), the activation atmosphere includes but is not limited to at least one of carbon dioxide and water vapor, the activation temperature is 800-1200° C., and the activation time is 5-20 hours.

Citation Information

Patent Citations

  • Process for preparing sphrical activated carbon by adding pore-forming agent

    CN1279125A

Cited By

  • Resin material as well as preparation method and application thereof

    CN120059398A

  • Preparation method of silicon-carbon composite negative electrode material capable of being quickly charged and lithium ion battery containing silicon-carbon composite negative electrode material

    CN121192136A

  • Irregular spherical porous carbon and preparation method and application thereof, and silicon-carbon composite material and preparation method and application thereof

    CN121449066A